莆仙戏的独特官形象 ：以《商辂教书》及《嵩口司》为例 = an analysis of the portrayals of officials in northern Fujian opera (Puxianxi) “Shanglujiaoshu” and “Songkousi” - 林英 Lin, Ying (2014)
中国福建省的莆田仙游地区孕育出中国古老地方剧种之一，莆仙戏。由于莆仙方言不易了解等原因，因而造成莆仙戏研究的局限。莆仙戏研究中较少涉及有关归类及分析剧本的方面，因此此领域仍待有研讨之处。本文将同是中国宝贵文化的莆仙戏和官文化结合在一起，探索这两者之间的关系；主要探讨官形象在莆仙戏中的展现。本文将首先以中国代表之一的“官文化”为着入点，探讨“官”与中国的密切关系。其次，本文将把现实与戏曲建立一个衔接，阐释官文化在戏曲中的表现，论及戏曲中传统官形象的塑造手法及其利与弊。再来，归类出莆仙戏中一些异于一般的特殊官形象，以及这些另类官形象所反映的文化现象及意义。最后，浅淡莆仙戏的前景及价值。Puxianxi is one of the traditional opera forms in Fujian Province and one of the longest running opera in Mainland China. Due to the geographical and language restrictions that Puxianxi is in, research involving Puxianxi is faced with much challenges and difficulties. Thus, this leads to the lack of Puxianxi’s research in many aspects, such as comparative studies between the different plays. This paper aims to contribute and fulfil parts in which the research is lacking by exploring the relationship between China’s “officialdom” culture and Puxianxi. This paper first inspects the “officialdom” culture in China, whereby “guan”or officials play a significant role in China’s culture. As opera is a platform of realism, plays involving officials roles are often seen in opera. I went on to discuss the extreme bipolar framework that officials characters are placed in and also the pros and cons behind this. After which, I will deal with some unique portrayal of officials in Puxianxi, which are formed due to the cultural background. The paper then ends off by reiterating the importance of Puxianxi and its future prospects.